An overview of the regulation of specialized metabolism in tobacco - Xia Wu; Sanjay Kumar Singh; Barunava Patra; Jing Wang; Sitakanta Pattanaik; Ling Yuan (Current Plant Biology)
Nicotiana tabacum (common tobacco) is an allotetraploid that presumably originated from the diploid ancestors of N. sylvestris and N. tometosiformis approximately 0.2 million years ago. Tobacco produces a diverse array of specialized metabolites (SM), including alkaloids, terpenoids, and flavonoids, and has been used as a model for studying the regulation of plant SM biosynthetic pathways. Nicotine, the primary pyridine alkaloid in tobacco, is synthesized in roots and transported through xylem to leaves. In addition to nicotine, tobacco produces three other pyridine alkaloids: anabasine, anatabine and nornicotine. Tobacco plants also accumulate various diterpenes, acylsugars, and phenolic compounds in the leaves, flowers and other tissues. Many genes encoding key enzymes involved in these SM pathways have been identified and characterized. Additionally, the transcription factors, such as those from the families of basic helix-loop-helix (bHLH), Apetala2/Ethylene Response Factor (AP2/ERF), MYB, and WRKY, have been identified as the major regulators of nicotine and flavonoid biosynthesis in tobacco. However, the regulation of diterpenes and acylsugar biosynthesis remains relatively underexplored. In addition to transcriptional regulation, SM pathways are also controlled by post-transcriptional and post-translational mechanisms, which have been less studied and discussed. In this review, we provide an overview of the molecular mechanisms governing biosynthesis of nicotine and phenolic compounds in tobacco, and we discuss future prospective and outstanding questions related to the regulation of these SM pathways. Understanding tobacco SM regulation has broad implications for plant biology, as it provides key insights into the regulation of metabolic pathways that produce important and structurally complex bioactive compounds.